Spatial Database open source o closed source? - Carlucci, Renzo; Bernardini, Fabrizio (GEOmedia, 2008)
Spatial Database for GIS: open source or closed source? Today's decision makers who do not have a geospatial information system (GIS) face critical challenges when making decisions pertaining to critical IT infrastructures. Decisions involving spatial components require detailed information, system-structure background and up-to-date IT knowledge. The objective of this paper is to review the fundamental concepts spatial databases used for geographic information systems (GIS) and a comparative analysis of current available software.